Counting CO2 emissions in a globalised world: producer versus consumer-oriented methods for CO2 accounting - Martin Bruckner; Christine Polzin; Stefan Giljum (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
This paper compares two different types of carbon accounting methods – measuring all emissions resulting from domestic production (the dominant method on which international carbon reduction targets are based) versus measuring the carbon emissions embodied in goods in the country where they are consumed (emissions from domestic production plus emissions embodied in imports minus emissions embodied in exports). Using a multi-regional input output (MRIO) model, we find that industrialised countries' emissions related to their consumption are higher than those related to their production activities, while the opposite is true for most emerging and developing countries. In order to devise fair and equitable climate policies it is worth analysing where and for what purpose greenhouse gases are emitted. We argue that consumption-based carbon accounts are a useful complement to production-based accounts. Comparing the results of both accounting methods may help in deciding how to allocate responsibility for emissions.
Keywords: 330